Meningkatkan Motivasi Dan Hasil Belajar Materi Sumber Daya Alam Kegiatan Ekonomi Melalui Penerapan Model Pembelajaran Problem Solving Berbantu Media Gambar Pada Siswa Kelas IV SD 5 Gondosari - Maskurin Maskurin (Universitas Muria Kudus, 2018)
Based on the results of observations on the initial conditions in 4th grade SD 5 Gondosari, data were obtained that the motivation and learning outcomes of students about the natural resources of economic activities were still very low. Student learning motivation is only 38% with completeness of learning outcomes only 44%. Therefore to improve this, carried out research by applying learning media image problem solving learning models. And the results obtained after carrying out research for two cycles were student learning motivation increased to 81%, and learning completeness by 88%.